1979
DOI: 10.1007/bf00424466
|View full text |Cite
|
Sign up to set email alerts
|

Optimal hematocrit for canine skeletal muscle during rhythmic isotonic exercise

Abstract: Contractile power, blood flow, O2-uptake, and O2-extraction during isotonic, rhythmic exercise were determined in the isolated canine gastrocnemius muscle during perfusion with blood with hematocrits between 0.21 and 0.81. The results obtained in 36 measurements on nine muscles showed that maximal O2-delivery to the muscle if found at hematocrits between 0.5 and 0.6. Both in the range of hemodilution, and in the range of extreme hemoconcentration, O2-delivery decreases significantly. O2-consumption and contrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
27
2

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 30 publications
4
27
2
Order By: Relevance
“…It should be noted, however, that this may vary under different circumstances because of the blood's non-Newtonian behavior (13). Factors affecting this variation include the species, the organs involved, and whether the organism is in resting or exercising conditions (11,12,(14)(15)(16). Thus, the above mentioned observations do not always reflect the general situation in exercising mammals and humans.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…It should be noted, however, that this may vary under different circumstances because of the blood's non-Newtonian behavior (13). Factors affecting this variation include the species, the organs involved, and whether the organism is in resting or exercising conditions (11,12,(14)(15)(16). Thus, the above mentioned observations do not always reflect the general situation in exercising mammals and humans.…”
mentioning
confidence: 89%
“…Because of these counteracting effects, it was suggested that the optimal Htc may be lower than expected because of limitations induced by a higher blood viscosity (8,(10)(11)(12). Although the role of Htc on exercise performance seems obvious, there is only one ex vivo study available addressing the above hypothesis in isolated higher vertebrate muscles (11). It should be noted, however, that this may vary under different circumstances because of the blood's non-Newtonian behavior (13).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…HD was then derived from HT by using literature data of the Fahraeus effect in vitro. 2 When capillaries were seen to form meshes creating divergent bifurcations downstream of a convergent bifurcation, only the initial capillary branch connected to the arteriolar tree was included in the analysis; less than 1% of all capillaries was seen to form such meshes. One network of the CTRL group and two networks of the HES group consisted of two arteriolar trees that could be analyzed independently.…”
mentioning
confidence: 99%
“…Haemodilution and a reduction in blood viscosity were associated with a significant increase in the mean partial pressure of oxygen in the tissues of organs studied. Results of a number of similar studies prompted further research to determine the optimal PCV, at which overall oxygen delivery to the tissues via hemoglobin transport is maximized, in veterinary patients undergoing general anaesthesia (Gaehtgens et al 1979, Fan et al 1980. However to date, the results of these studies have been variable and an optimal PCV has not yet been determined …”
Section: Page 46mentioning
confidence: 99%